2021
DOI: 10.1016/j.amjsurg.2020.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Is the placement of jejunostomy tubes in patients with esophageal cancer undergoing esophagectomy associated with increased inpatient healthcare utilization? An analysis of the National Readmissions Database

Abstract: Background: Patients undergoing esophagectomy often receive jejunostomy tubes (j-tubes) for nutritional supplementation. We hypothesized that j-tubes are associated with increased postesophagectomy readmissions. Study design: We identified esophagectomies for malignancy with (EWJ) or without (EWOJ) j-tubes using the 2010e2015 Nationwide Readmissions Database. Outcomes include readmission, inpatient mortality, and complications. Outcomes were compared before and after propensity score matching (PSM). Results: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Multiple studies reported no or limited differences in postoperative complications and mortality between patients with and without FJs [ 9 , 21 , 22 , 23 ]. A recent meta-analysis (4594 patients) investigated the application of FJs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reported no or limited differences in postoperative complications and mortality between patients with and without FJs [ 9 , 21 , 22 , 23 ]. A recent meta-analysis (4594 patients) investigated the application of FJs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individual institutions vary in preference for or against routine jejunostomy placement at the time of oesophagectomy (Álvarez-Sarrado et al 2019, Ireland & Jaunoo 2020, Purkayastha et al 2019). The optimal route of nutrition immediately postoperatively after oesophagectomy remains to be determined (Carroll et al 2020, Holmén et al 2020, Zheng et al 2021). Current data suggest that an individualized approach to postoperative nutrition that accounts for patient nutritional status and surgery technique should be used (Zheng et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Diese Erweiterung des laparoskopischen Eingriffs hat jedoch in unizentrischen Untersuchungen eine signifikante Morbidität gezeigt, da bei über 20 % dieser Patienten eine Katheterdysfunktion diagnostiziert wird und mehr als 2 % erneut operiert werden müssen [37]. Die Auswertung eines nationalen Registers kommt jedoch zu dem Ergebnis, dass die Wiederaufnahme und Mortalität durch die Anlage einer Katheterjejunostomie nicht erhöht wird [38]. Zusammenfassend gibt es gegenwärtig keinen allgemein akzeptierten Algorithmus zum postoperativen Ernährungsmanagement und zur Prophylaxe/Therapie des DGCE, die das führende Problem bei der Implementierung von Fast-Track-Protokollen bleiben.…”
Section: Anästhesiologisches Managementunclassified